An analysis of the law governing the acquisition of shipwreck - Bruk, Judian (Institute of Marine and Environmental Law, 2021)
The second half of the twentieth century has brought drastic changes in technology. These advances have changed the way marine resources are harvested or acquired The development of SCUBA made diving to depths of 50m unrestrained by the need for surface support, feasible. 1 This opened up the possibility of exploring below the surface of the sea. It also brought with it the possibility of salvaging wrecks and remains which had been hidden since antiquity.2 The year 1954 saw the first stem trawler the Fairtry converted from a decommissioned whaler. She was to set the standard for trawling efficiency and her design was soon replicated, replacing other types. 3 Nylon fibres made lines and nets lighter and more durable.